2011
DOI: 10.1371/journal.pone.0021874
|View full text |Cite|
|
Sign up to set email alerts
|

The Tissue Microlocalisation and Cellular Expression of CD163, VEGF, HLA-DR, iNOS, and MRP 8/14 Is Correlated to Clinical Outcome in NSCLC

Abstract: BackgroundWe have previously investigated the microlocalisation of M1 and M2 macrophages in NSCLC. This study investigated the non-macrophage (NM) expression of proteins associated with M1 and M2 macrophages in NSCLC.MethodsUsing immunohistochemistry, CD68+ macrophages and proteins associated with either a cytotoxic M1 phenotype (HLA-DR, iNOS, and MRP 8/14), or a non-cytotoxic M2 phenotype (CD163 and VEGF) were identified. NM expression of the markers was analysed in the islets and stroma of surgically resecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
26
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 40 publications
3
26
0
Order By: Relevance
“…Here, lung tissues from patients with NSCLC (adenocarcinoma, squamous cell lung carcinoma and large cell lung carcinoma) were used to investigate M1 and M2 marker expression in TAM populations within tumour and non-tumour tissue using immunohistochemistry (IHC). Various studies have demonstrated increased TAM infiltration in NSCLC using the CD68 macrophage marker [21,22,20,23,19] with some suggesting the presence of increased macrophage numbers is a powerful predictor of survival in NSCLC [19,24,9]. In our study, all NSCLC subtypes were found to have significantly more CD68-positive cells when compared to non-tumour tissues.…”
Section: Discussionsupporting
confidence: 59%
“…Here, lung tissues from patients with NSCLC (adenocarcinoma, squamous cell lung carcinoma and large cell lung carcinoma) were used to investigate M1 and M2 marker expression in TAM populations within tumour and non-tumour tissue using immunohistochemistry (IHC). Various studies have demonstrated increased TAM infiltration in NSCLC using the CD68 macrophage marker [21,22,20,23,19] with some suggesting the presence of increased macrophage numbers is a powerful predictor of survival in NSCLC [19,24,9]. In our study, all NSCLC subtypes were found to have significantly more CD68-positive cells when compared to non-tumour tissues.…”
Section: Discussionsupporting
confidence: 59%
“…Consistent with these findings, an overexpression of S100A8 and/or S100A9 significantly correlates with tumor progression and worse outcome in the patients with breast cancer, prostate cancer, bladder cancer, and colon cancer (8)(9)(10)(11)(12). In contrast, several studies reported that the expression is associated with tumor response to chemotherapy in cervical cancer and also correlates with a good prognosis in gastric and lung cancers (13)(14)(15)(16). Therefore, whether an upregulation of S100A8/A9 in tumors predicts a good or poor prognosis in the clinical setting is still controversial.…”
mentioning
confidence: 69%
“…5D showed a significantly higher percentage of CD163/ CD206 positive cells in DEN C HF-HC-HSD mice suggesting that these M2 macrophages indeed represent the TAMs in our experimental model. Apart from CD163, several other TAM markers such as IL-10, iNOS, and VEGF have been used for diagnosis of tumor staging in lung, 38 breast, 39 and colon cancers. 40 The upregulation of CD163, VEGF, and IL-10 and the downregulation of iNOS in LMNCs indicates the presence of M2-like TAMs in our experimental model.…”
Section: Discussionmentioning
confidence: 99%